THE RELATIONSHIP BETWEEN SOCIAL SUPPORT, SPIRITUALITY WITH STRESS TOWARDS THE BURDEN OF FAMILY CAREGIVERS OF CANCER PATIENTS: A LITERATURE REVIEW - Hesti Rahayu; Sri Yona (Alta Dharma Publisher, 2019)
Cancer is a non-communicable disease that causes the second-highest death in the world. The study aimed to examine the relationship between social supports, spirituality with stress towards the burden of family caregivers of cancer patients. We searched literature from various relevant sources such as Ebsco, Science Direct, PubMed, and BMC Medicine, which published from 2012 to 2018. The results showed that social support reduced the stress of family caregivers. Spirituality could be as the coping for the family caregivers in dealing with stress. The factors associated with the high burden of family caregivers of cancer patients included age, cognitive as well as the family caregivers characteristics’. Further studies need to conduct spiritual and social support intervention to examine the effect of the intervention on health outcomes. Keyword: social support, spirituality, stress, caregiving burden, family caregivers of cancer patients. .